Principal Leadership and Teacher Performance Improvement: Findings from a Case Study in Wajo Regency - Asriani, Besse; Herlina, Besse; Syamsiar, Syamsiar; Arafah, Muhammad (LP3M, Universitas Muhammadiyah Kendari, 2024)
This study aims to explore the role of the school principal as a teacher leader in enhancing teacher performance at UPTD SDN 360 Anabanua, Maniangpajo District, Wajo Regency. Using a qualitative case study approach, data were collected through in-depth interviews with the school principal and selected teachers, observations, and document analysis. Findings indicate that the school principal plays a pivotal role in enhancing teacher performance by offering continuous motivation, personalized guidance, resource provision, and emotional support. These leadership practices foster a positive work environment, contributing significantly to improved teacher performance and student outcomes. The study underscores the school principal's role as a transformative leader, essential for driving educational quality improvements in elementary schools. The findings suggest that investing in leadership development for school principals could be a key strategy to advance educational excellence